2012
DOI: 10.1093/imammb/dqs025
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of intestinal oedema formation

Abstract: Intestinal oedema is a medical condition referring to the build-up of excess fluid in the interstitial spaces of the intestinal wall tissue. Intestinal oedema is known to produce a decrease in intestinal transit caused by a decrease in smooth muscle contractility, which can lead to numerous medical problems for the patient. Interstitial volume regulation has thus far been modelled with ordinary differential equations, or with a partial differential equation system where volume changes depend only on the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…It has been demonstrated that these devices can affect the local temperature of internal colon layers, thus leading to unexpected and undesirable effects similar to POI drawbacks. On this line, in particular, hyperelastic-based models are being studied for applications in medical robotics (20,30), taking into account the internal irregularities of intestinal villi (3), intestinal edema (74), and viscoelasticity (10,67). The effect of temperature may play an interesting role in most of these open problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that these devices can affect the local temperature of internal colon layers, thus leading to unexpected and undesirable effects similar to POI drawbacks. On this line, in particular, hyperelastic-based models are being studied for applications in medical robotics (20,30), taking into account the internal irregularities of intestinal villi (3), intestinal edema (74), and viscoelasticity (10,67). The effect of temperature may play an interesting role in most of these open problems.…”
Section: Discussionmentioning
confidence: 99%
“…Biot's seminar work [6][7][8] laid the foundation of the theory of poroelasticity, which models the the interaction between the fluid flow and deformation in an fluid-saturated porous medium. The model is used in several industries such as petroleum and environmental engineering [46,55] and medical applications such as the modeling of the intestinal oedema [54].…”
Section: Introductionmentioning
confidence: 99%
“…The time-dependent coupling of flow through a porous medium with elastic deformation is referred to as poroelasticity. The modeling of poroelastic deformation is central to applications in a variety of fields including biomechanics [20,24,25], reservoir engineering, and environmental engineering. The poroelasticity equations were first set forth in the work of Terzaghi [21] and Biot [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive derivations of balance equations for porous media, with constitutive equation assumptions, including those for compressible and incompressible liquids, gasses, multiphase media, linear elastic response, and thermal effects can be found in the literature [1,11]. Direct derivations of Biot's model, from a macroscopic vantage point, are also readily available [13,19,25] in addition to details regarding the existence and uniqueness of weak solutions [19,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation